TINJAUAN TENTANG UPACARA PERNIKAHAN DAN TATA RIAS PENGANTIN SOLO PUTRI DI KOTA PADANG SUMATERA BARAT - Eka Putri, Nela Aprilia; Hayatunnufus, Hayatunnufus; Astuti, Murni (Journal of Home Economics and Tourism, 2017)
This research is motivated by the many cultural diversity that exist in Indonesia, one of the wedding ceremony and bridal makeup of Java in Padang city of West Sumatra. The focus of this research is the wedding ceremony, makeup, the bun and the wedding dress of Solo Putri in Padang City. The purpose of the researchers conducted this study to know more clearly about the wedding ceremony and makeup of Solo Putri bride in the city of Padang, West Sumatra. This research uses qualitative research methods in order to dig deeper marriage ceremony and makeup of Solo Putri bride in Padang city of West Sumatra. The object of this research is the wedding ceremony and bridal makeup. The results of this study found that the traditional wedding ceremony Solo Princess is the same as that in Java, only in the city of Padang is not implemented throughout the series of wedding ceremonies.